2016
DOI: 10.2174/1871527315666160413121751
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Nitric Oxide in Autism Spectrum Disorder and Other Neuropsychiatric Disorders

Abstract: The etiology of autism spectrum disorder (ASD) remains unclear; however, the toxic environmental exposure to oxidative stress has been suggested to play an important role in its pathogenesis. A loss of balance between oxidative stress and antioxidant capacity produces an excess of reactive nitrogen species (RNS) such as nitric oxide (NO). Polyunsaturated fatty acids (PUFAs), particularly arachidonic acid, docosahexaenoic acid and eicosapentaenoic acid, are closely related to NO and NO synthase. In the pathophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 0 publications
1
48
0
1
Order By: Relevance
“…Preeclampsia is one of the leading causes of maternal morbidity and mortality and has recently been redefined by the International Society for the Study of Hypertension in Pregnancy (ISSHP) as newonset hypertension (blood pressure ≥140/90 mmHg on/after 20 weeks' gestation) accompanied by proteinuria and/or other maternal organ dysfunction and/or uteroplacental dysfunction (Brown et al, 2018). Preeclampsia is associated with maternal inflammation, poor placentation and oxidative stress, which may also represent some of the potential aetiological pathways in the development of ASD (Brown et al, 2014;Nomura et al, 2017;Yui, Kawasaki, Yamada, & Ogawa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia is one of the leading causes of maternal morbidity and mortality and has recently been redefined by the International Society for the Study of Hypertension in Pregnancy (ISSHP) as newonset hypertension (blood pressure ≥140/90 mmHg on/after 20 weeks' gestation) accompanied by proteinuria and/or other maternal organ dysfunction and/or uteroplacental dysfunction (Brown et al, 2018). Preeclampsia is associated with maternal inflammation, poor placentation and oxidative stress, which may also represent some of the potential aetiological pathways in the development of ASD (Brown et al, 2014;Nomura et al, 2017;Yui, Kawasaki, Yamada, & Ogawa, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A recent wealth of evidence has demonstrated that free radicals, and most notably NO, play a crucial role in the regulation of stress effects and may be directly involved in the pathophysiology of stress-related disorders [13][14][15][16][17]. Under normal conditions, NO produced by the neuronal isoform of nitric oxide synthase (nNOS) is an important neurotransmitter associated with synaptic plasticity, memory formation, and neurotransmitter release [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies indicate higher oxidant factors in children with autism. 20,21 Increased nitric oxide (NO) has been consistently demonstrated. 20 Increased thiobarbituric acid reactive substances (TBARS), the degradation products of fats, and increased xanthine oxidase activity in red blood cells have also been reported in autistic patients, 21 as have higher levels of the lipid peroxidation biomarker 8-isoprostane (8-iso-PGF2α).…”
Section: Resultsmentioning
confidence: 99%
“…20,21 Increased nitric oxide (NO) has been consistently demonstrated. 20 Increased thiobarbituric acid reactive substances (TBARS), the degradation products of fats, and increased xanthine oxidase activity in red blood cells have also been reported in autistic patients, 21 as have higher levels of the lipid peroxidation biomarker 8-isoprostane (8-iso-PGF2α). 19 Higher levels of these compounds in autistic individuals are clear indicators of elevated oxidants which may lead to cell degradation and death.…”
Section: Resultsmentioning
confidence: 99%